Perhitungan Bandwith Dan Spesifikasi Client Server Local Meeting Untuk Mengatasi Lonjakan Trafic - Yulianton, Heribertus; Priambodo, Ilyas; Listiyono, Hersatoto (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The Pandemic period had an impact on the meeting system at dr. Kariadi Hospital where internal meetings which are usually held face-to-face are now required through virtual media. To overcome the excessive use of the internet, a local meeting server was created using the Linux Debian Buster Operating System and the OpenMeetings Application System. This study aims to find local meeting server resources that suit the needs to be comfortable to use by users. To achieve the  convenience  and  its application  in  using  the  meeting  server  application  required  resources.  Multiple Linear Regression predicts the amount of bandwidth by using computer resource usage data on the number of application users. By creating a local meeting server and calculating server resources, it helps to expedite and make it easier to carry out meetings that must be held in different places.